2011
DOI: 10.1017/s0007114511003023
|View full text |Cite
|
Sign up to set email alerts
|

Low fruit and vegetable consumption in Mozambique: results from a WHO STEPwise approach to chronic disease risk factor surveillance

Abstract: Monitoring food consumption and its determinants over time is essential for defining and implementing health promotion strategies, but surveillance is scarce in Africa. The present study aimed to describe fruit and vegetable consumption in Mozambique according to sociodemographic characteristics and place of residence (urban/rural). A national representative sample (n 3323) of subjects aged 25-64 years was evaluated in 2005 following the WHO Stepwise Approach to Chronic Disease Risk Factor Surveillance, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
44
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 26 publications
11
44
2
2
Order By: Relevance
“…These rates seem to be similar to a previous survey among the adult population in South Africa (4) and in a study among older adults in Northern Ireland (10), but the prevalence rate of insufficient FV intake was lower in this study than among elderly populations in several Asian countries (5), Mozambique (7), and Iran (8) and it was higher than in Canada (9). Unlike other studies (1116), the prevalence of low FV intake was higher (although not significantly) among female than male older adults in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These rates seem to be similar to a previous survey among the adult population in South Africa (4) and in a study among older adults in Northern Ireland (10), but the prevalence rate of insufficient FV intake was lower in this study than among elderly populations in several Asian countries (5), Mozambique (7), and Iran (8) and it was higher than in Canada (9). Unlike other studies (1116), the prevalence of low FV intake was higher (although not significantly) among female than male older adults in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies among the adult population in South Africa in 2003 found that 72.2% of men and 66.7% of women had low FV consumption (5) and in a local study, 7% of the villagers and none of the semi-urban dwellers reported the recommended five or more FV servings per day (6). In a more recent study among adults (25–64 years) in Mozambique, less than 5% of the subjects reported an intake of five or more daily servings of FVs (7). In Iran, a middle-income country, low mean number of FV servings per day (1.76) among persons aged 60 and above were reported (8), while in some high-income countries, lower rates of FV intake was found among older adults, for example, 47% in Canada (9) and a mean consumption of 4.0 and 4.1 portions of FVs per weekday and per weekend day, respectively, in Northern Ireland (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate consumption, however, is most commonly seen in many countries in SSA,22 and our findings are no exception. Approximately one out of every seven adults reported daily fruit or vegetable consumption while most people reported consuming fruits or vegetables 2–3 days per week.…”
Section: Discussionsupporting
confidence: 57%
“…The present community-based cross-sectional study evaluated a representative sample of the Mozambican adults aged 25 to 64 years, between September and November 2005, as previously described in detail (Padrão et al, 2011(Padrão et al, , 2012. Briefly, the survey followed a complex sampling design with clustering at a geographical unit level and at the household level, as well as stratification by province.…”
Section: Methodsmentioning
confidence: 99%